1995
DOI: 10.1136/jamia.1995.96073833
|View full text |Cite
|
Sign up to set email alerts
|

The Columbia Registry of Information and Utilization Management Trials

Abstract: Objective: To systematically locate, register, and abstract information used in comparing effects of various information services (computerized and noncomputerized) and utilization management interventions on the process and outcome of patient care.Design: Manual and electronic database searches located reports that met three main criteria: 1) randomized controlled trial; 2) information or utilization management intervention in the study group with no similar intervention in the control group; and 3) effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At the University of Missouri, the Columbia Registry of Medical Management Trials provides a unique source of randomized clinical trials for meta-analyses, traditional reviews, and executive summaries for quality improvement of health services. A study concluded that with the emergence of computerized electronic networks, clinicians and physician executives gaining direct access to bibliographic databases could be better served by structured indexing of critical aspects of randomized controlled clinical trials: design, sample, intervention, and effects [2]. Based on a large sample of randomized controlled clinical trials of organizational interventions, a study analyzed the various methods of such trials and identified the special requirements of applying randomized trials in health services research [23].…”
Section: Seeking Conclusive Knowledgementioning
confidence: 99%
“…At the University of Missouri, the Columbia Registry of Medical Management Trials provides a unique source of randomized clinical trials for meta-analyses, traditional reviews, and executive summaries for quality improvement of health services. A study concluded that with the emergence of computerized electronic networks, clinicians and physician executives gaining direct access to bibliographic databases could be better served by structured indexing of critical aspects of randomized controlled clinical trials: design, sample, intervention, and effects [2]. Based on a large sample of randomized controlled clinical trials of organizational interventions, a study analyzed the various methods of such trials and identified the special requirements of applying randomized trials in health services research [23].…”
Section: Seeking Conclusive Knowledgementioning
confidence: 99%
“…The Columbia Registry is a systematic collection of medical management trials at the University of Missouri, School of Medicine. 9 Extensive searches were done to collect all additional relevant controlled clinical trial reports: bibliographic database retrievals (eg, MEDLINE, CINAHL, HEALTH), manual searches (monographs, unindexed publications, reference lists), and informal contacts. By mapping the eligibility criteria, the search strategy for the collection of trials on prompting included a combination of medical subject heading (MeSH) terms and textwords (TWs) for each eligibility criterion.…”
Section: Collection Of Reportsmentioning
confidence: 99%